Athanasius of Alexandria and Gregory of Nazianzus: theopoiēsis and theōsis - McLoone, Daniel P. (2021)
This study explores the often-posited distinction between Alexandrian and Cappadocian approaches to deification in the fourth and fifth centuries. Athanasius of Alexandria has been selected to represent an Alexandrian approach and Gregory of Nazianzus, to represent a Cappadocian one. Comparison of their respective theologies of deification reveals a diversity in opinion on what exactly deification involved among the Fathers and the inadequacy of the interpretive categories of “moral” and “realistic” approaches to distinguish between them. The study observes areas of convergence and divergence at each stage of their respective narratives of deification, beginning with Creation and the Fall; then the Redemptive work of Christ; Pneumatology and Baptism; the Christian life, and finally the Deified State. What should become apparent throughout this study is that while both Fathers are espousing ideas which should rightfully be considered deification, the substance of their ideas and their focuses differ dramatically in places and while they are not necessarily contradictory or unsynthesizable, it is necessary to recognise their significant differences.